GnRHa protects the ovarian reserve by reducing endoplasmic reticulum stress during cyclophosphamide-based chemotherapy - Xiaolin Li (Nature Portfolio, 2021)
Abstract Chemotherapy-induced ovarian dysfunction is a serious adverse effect in premenopausal patients with cancer. Gonadotrophin-releasing hormone analogs (GnRHa) protect ovarian function, but its molecular mechanisms have not yet been determined. In this study, we attempted to determine the previously unknown molecular mechanism by which such protection occurs. Serum anti-Müllerian hormone (AMH) levels were tested in tumor-bearing nude mice, a series of exploratory experiments were conducted. We discovered that GnRHa protects granulosa cells from chemotherapeutic toxicity in vivo and in vitro. We also showed that CTX-induced endoplasmic reticulum stress inhibits the secretion of AMH, and treatment with GnRHa relieves ER stress and the subsequent unfolded-protein response by modulating mTOR signaling to induce autophagy. The results of mechanistic studies indicated that GnRHa-modulated mTOR signaling to induce autophagy, which alleviated CTX-induced ER stress and promoted the secretion of AMH.